Knowledge of the Pillars of Industry 4.0 in the Polish Steel Industry - Bożena GAJDZIK (Communications of International Proceedings, 2021)
The article presents a part of the results of direct research conducted among enterprises of the steel industry in Poland. The research falls under the exploratory research category and was conducted using a questionnaire last year (just before the outbreak of the COVID-19 pandemic). The results of the research create knowledge about the transformation of steel industry enterprises towards Industry 4.0. The new industrial concept brings together many of the breakthrough technologies of the fourth industrial revolution. Enterprises build cyber-physical production systems, analyse large data sets, use decentralized control systems for manufacturing processes, and cooperate without time and space limitations. The specific technologies of Industry 4.0 are challenges for the steel industry. Economic, digital and technological developments as well as energy efficiency requirements pose many challenges for the European steel industry. New and stricter energy efficiency and emissions rules to protect Europe's environment in tandem with the development of societies and economies will have an impact on the way the steel sector works. In order to meet all these challenges, innovations in the functioning of steelworks are needed. Knowledge among producers of the steel industry in Poland of the key technologies of Industry 4.0 is the basis for building Industry 4.0.
Keywords: Poland; steel industry; Industry 4.0.